2018
DOI: 10.1002/nau.23703
|View full text |Cite
|
Sign up to set email alerts
|

Refined nomogram incorporating standing cough test improves prediction of male transobturator sling success

Abstract: MSIGS adds prognostic value to PPD in assessing success of transobturator sling for treatment of SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…Physicians offering different treatment options tend to consider AUS in the more complex patient [20]. No decision-assisting algorithm has been developed to help clinicians in the choice to use one device or another, but the cough test has been recently proposed to improve prediction of success in patients undergoing a male sling procedure [21]. In our study, the decision to use one or the other device was based on patient preference and counselling with physical examination and cough test.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians offering different treatment options tend to consider AUS in the more complex patient [20]. No decision-assisting algorithm has been developed to help clinicians in the choice to use one device or another, but the cough test has been recently proposed to improve prediction of success in patients undergoing a male sling procedure [21]. In our study, the decision to use one or the other device was based on patient preference and counselling with physical examination and cough test.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients with incomplete preoperative MSIGS or post-operative follow-up data. SUI severity was defined by the preoperative pads per day (PPD) usage: 0-1 PPD=mild; 2-3 PPD=moderate; ≥4 PPD=severe; these definitions are based on our prior study on risk factors for sling failure (18). For this sub--analysis, we excluded patients with mild and severe SUI and focused solely on the patients with moderate SUI.…”
Section: Methodsmentioning
confidence: 99%
“…Patients found to have unfavorable moderate SUI could then be informed of the low success rate of sling and encouraged to consider an AUS. We have previously demonstrated that the SCT adds predictive value for sling success for patients who already have PPD and 24-hour pad weight measurements (18).…”
Section: Male Sui Assessmentmentioning
confidence: 97%
See 2 more Smart Citations